UPAYA MELATIH JIWA KEPEMIMPINAN PADA ANAK USIA DINI MELALUI BIG PUZZLE - Anita Istiningtyas; Wahyuningsih Safitri (Jurnal Pengabdian Kepada Masyarakat Ungu( ABDI KE UNGU), 2020)
Leadership character building is not widely applied in preschool education. The problem that still occurs is lack of teachers’ understanding with the essence of national education is to make humans holistic and have character. According to research it is known that teacher’s insight about character building learning methods according to preschool development are still lacking. One of the methods that can be taught to train leadership skill in preschool according to guide of regulation of the minister of education and culture is Big Puzzle method. The purpose of this activity is to teach the teacher about big puzzle method to train leadership skill in preschool. The method in this activity is demonstration and discussion. The result of this activity is an increase in the mean of the teacher knowledge by 87% about the big puzzle learning method. This activity is expected to be applied in learning to students so that it hones leadership skill which must be raised with an interesting learning media.